Introduction to wireless and mobile systems - Agrawal, Dharma Prakash (Cengage Learning, 2008)
Introduction to wireless and mobile systems / Agrawal, Dharma Prakash. -- New Delhi: Cengage Learning, 2008 621.384 Ag261e2 2nd ed. No. of Copies : 1